Investigating the common factors in welding defects of metal connections: تحقيق العوامل المشتركة في عيوب اللحام للوصلات المعدنية - Islam Nazak Hamed Ragab, Tariq Ibrahim Muhammad Al- Nakhilan (Journal of engineering sciences and information technology, 2022)
There are many reasons that lead to the occurrence of defects and errors in the welding process, and many researches have talked about this and concluded for several factors, some of which are technical related to the conditions of the welding process, and some are related to the skill of the worker himself, and others are related to the factors surrounding the welding process and metallurgical changes. The common factors of aspects of the welding process, which would lead to errors in the welding process by identifying the basics of obtaining a good welding line and identifying them in points and then changing these basics and recording the difference by means of simple destructive tests and then coming up with common fixed points that are classified as the basis for not obtaining good welding lines This is in order to avoid the technician and the specialist for these reasons, and let it be a scientific subject taught to those interested in welding operations. The experiment was done on steel of the low carbon type as a result of its high welding ability. Electric arc welding was chosen for its spread in several fields. With the choice of the flat horizontal position for these tests. The study ended with the verification of three common factors that would be the main causes in the various welding operations, which are the presence of oxides and impurities in the welding metal, the lack of skill of the technical worker, and the conduct of welding operations in an atmosphere of air current.